Profil Kematangan Karier Mahasiswa STAI Siliwangi Bandung - Ahmad Rifqy Ash-Shiddiqy (Indonesian Journal of Educational Counseling, 2018)
PROFILE OF STUDENTS CAREER MATURITY STAI SILIWANGI BANDUNG. This study is driven by the tendency of guidance and counseling services at universities, especially in STAI Siliwangi Bandung by students to establish their future career maturity, nevertheless, the services obtained do not meet their expectations. Considering career guidance for students, especially student career maturity is left alone, passes, and runs by itself. Then students will experience confusion and unpreparedness in facing the next career demands. Students are the final status as learners before entering the world of work and following career demands, so they need direction, career guidance to stimulate the development and stabilization of their career orientation optimally according to the level and characteristics typical of the progress as it goes through. The purpose of this research is the formation of the maturity profile of the student's career. This research uses the quantitative method. This research produces (1) Maturity picture of Student Career (2) The effectiveness of career counseling to strengthen the maturity of the student's career. The conclusion of the research is the maturity of the student's career is in mature category, there is no career guidance service to strengthen student career maturity in STAI Siliwangi Bandung, based on the results of research can be formulated a model of collaborative career guidance services to harden the maturity of STAI Siliwangi Bandung student career.